INTEGRASI ILMU PENGETAHUAN DAN TEKNOLOGI - Ayu Nur Chamidah; Ari Abi Aufa (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The development of science and technology (IPTEK) in the modern era has brought significant changes to various aspects of human life. This article discusses the reciprocal relationship between science and technology, in which science serves as the theoretical foundation for the emergence of technology, while technology functions as a means of applying and accelerating the development of scientific knowledge. Using a qualitative research method with a library research approach, data were collected from books, articles, and scientific journals relevant to the theme of science, technology, and their implications for society, particularly in the field of education. The findings indicate that science and technology play a strategic role in facilitating human activities, increasing the effectiveness of learning processes, and serving as an indicator of a nation's progress. However, the advancement of science and technology also entails potential negative impacts such as digital inequality, technological dependence, and ethical as well as moral issues. Therefore, the development and utilization of science and technology must be accompanied by the strengthening of ethical values, social responsibility, and human character so that their progress results not only in technical sophistication but also in genuine benefits for human life.